1996
DOI: 10.1007/bf02355065
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous development of Crohn's disease and myelodysplastic syndrome progressing to acute myelocytic leukemia in a patient with a normal karyotype

Abstract: A 28-year-old man developed Crohn's disease and myelodysplastic syndrome concurrently. Chromosomal analysis of the bone marrow revealed a normal male karyotype. Subsequently, the myelodysplastic syndrome progressed to acute myelocytic leukemia. Several causes, including the medical treatment for Crohn's disease, chromosomal abnormalities, and a common underlying immune dysfunction, have been proposed as pathogenetic factors in the association with Crohn's disease of hematologic malignancies. This case suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…[5][6][7][8][9][10] Characteristics of those 10 cases, and of the seven cases presented here are shown in Table 1. Nine patients (53%) were male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10] Characteristics of those 10 cases, and of the seven cases presented here are shown in Table 1. Nine patients (53%) were male.…”
Section: Discussionmentioning
confidence: 99%
“…4 Recently, a few patients with both IBD (Crohn's disease or ulcerative colitis) and MDS have been reported, and it was suggested that the association between the two disorders was not fortuitous. [5][6][7][8][9][10][11][12] We report here seven additional cases associating MDS and IBD, and review previously published cases.…”
Section: Introductionmentioning
confidence: 99%
“…However, when leukopenia and thrombocytopenia are present, the possibility of other concomitant diseases (such as idiopathic thrombocytopenic purpura and pancytopenia caused by drugs) should be considered. In recent years, there have been some reports of concurrent IBD with leukemia and myelodysplastic syndrome (MDS) [2][3][4][5][6][7][8][9], but concurrent IBD and MDS cases are rare. In this study, we report nine patients with concurrent MDS and IBD treated between January 1985 and October 2006.…”
Section: Introductionmentioning
confidence: 99%
“…The time to onset between the initiation of AZA therapy and AL is often inconclusive (highly variable). Finally, in some patients the development of AL did precede CD [30,31] or can occur in the absence of AZA [18,30,32,33,34]. However, the association between IBD and AL has been suggested since the 1990’s [3].…”
Section: Discussionmentioning
confidence: 99%